Peter Asher a life in music - Jacks, David S. 1975- (Backbeat, 2022)
"An in-depth look at the life and career of one of the most unique figures in the music industry and his success as a hit-making artist, a hit-making producer, and a manager for hit-making talent"--
Includes index
Keywords: Asher, Peter -- 1944-; Asher, Peter / 1944-; Peter and Gordon; Singers / United States / Biography; Sound recording executives and producers / United States / Biography; Singers / England / Biography; Sound recording executives and producers / England / Biography; Popular music / History and criticism; Chanteurs / États-Unis / Biographies; Chanteurs / Angleterre / Biographies; Producteurs d'enregistrements sonores / Angleterre / Biographies; Musique populaire / Histoire et critique; Popular music; Singers; Sound recording executives and producers; England; United States; Biographies; Criticism, interpretation, etc; Biografie